KUALITAS KEPUASAN KERJA DAN MOTIVASI KERJA MEMEDIASI KEHIDUPAN KERJA TERHADAP KINERJA KARYAWAN - Eka Sekar Ayu Pratiwi; Koko Safitri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Providing the right motivation and creating a good quality of working life, fostering organizational commitment for employees so as to create job satisfaction and have an effect on improving employee performance. This study aims to examine the effect of quality of job satisfaction on Performance Through Job Satisfaction and Work Motivation. This research at PT. Bumihutani Lestari Katingan Regency using primary and secondary data. The analytical techniques in this study use SEM-PLS. The results in this study that the quality of work life does not significantly affect performance but will have an effect if mediated by job satisfaction and work motivation. With the result that improvement in performance of working life will increase if mediated by job satisfaction and work motivation.